BIOSYNTHESIS OF TRUNCATED N-LINKED OLIGOSACCHARIDES RESULTS FROM NON-ORTHOLOGOUS HEXOSAMINIDASE-MEDIATED MECHANISMS IN NEMATODES, PLANTS AND INSECTS - Gutternigg, Martin (2007)
In many invertebrates and plants, the N-glycosylation profile is dominated by truncated paucimannosidic N-glycans, i.e., glycans consisting of a simple trimannosylchitobiosyl core often modified by core fucose residues. Even though they lack antennal N-acetylglucosamine residues, the biosynthesis of these glycans requires the sequential action of GlcNAc transferase I, Golgi mannosidase II and, finally, β-N-acetylglucosaminidases. In Drosophila, the recently characterised enzyme encoded by the fused lobes (fdl) gene specifically removes the non-reducing N-acetylglucosamine residue from the α1,3-antenna of N-glycans. In the present study, we examined the products of five β-N-acetylhexosaminidase genes from Caenorhabditis elegans (hex-1 to hex-5, corresponding to reading frames T14F9.3, C14C11.3, Y39A1C.4, Y51F10.5 and Y70D2A.2) in addition to three from Arabidopsis thaliana (AtHEX1, AtHEX2 and AtHEX3, corresponding to reading frames At1g65590, At3g55260 and At1g05590). Based on homology, the Caenorhabditis HEX-1 and all three Arabidopsis enzymes are members of the same sub-family as the aforementioned Drosophila fused lobes enzyme, but either act as chitotriosidases or non-specifically remove N-acetylglucosamine from both N-glycan antennae. The other four Caenorhabditis enzymes a members of a distinct sub-family; nevertheless, two of these enzymes displayed the same α1,3-antennal specificity as the fused lobes enzyme. Furthermore, a deletion of part of the Caenorhabditis hex-2 gene drastically reduces the native N-glycan-specific hexosaminidase activity in mutant worm extracts and results in a shift in the N-glycan profile, which is a demonstration of its in vivo enzymatic relevance. Based on these data, it is hypothesised that the genetic origin of paucimannosidic glycans in nematodes, plants and insects involves highly-divergent members of the same hexosaminidase gene family.